2005
DOI: 10.1590/s1677-55382005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum level of prostate-specific antigen adjusted for the transition zone volume in early detection of prostate cancer

Abstract: Objective: To determine the clinical usefulness of prostate-specific antigen (PSA) density in the transition zone (PSADTZ) for increasing the specificity in early detection of prostate cancer (PCa) and reducing unnecessary biopsies in males with PSA between 4.0 and 10 ng/mL. Materials and Methods: This cross-sectional study obtained PSADTZ measurements in 68 patients with PSA between 4.0 and 10 ng/mL. All patients underwent transrectal ultrasonography (TRUS) with biopsies. PSADTZ was estimated by dividing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…As in the article of Djavan et al (13) in this study, in the multivariate analysis the PSADTZ and the %FPSA, were the two variables most strongly predictors of PCa, being that the PSADTZ was the variable that presented the largest predicting power, concurring with the result of the others (2,4,6,7,13,16,19).…”
Section: Commentssupporting
confidence: 82%
See 2 more Smart Citations
“…As in the article of Djavan et al (13) in this study, in the multivariate analysis the PSADTZ and the %FPSA, were the two variables most strongly predictors of PCa, being that the PSADTZ was the variable that presented the largest predicting power, concurring with the result of the others (2,4,6,7,13,16,19).…”
Section: Commentssupporting
confidence: 82%
“…Kikuchi et al (16) found a superiority of the concept of PSADTZ in relation to %FPSA, however the PSADTZ was not better than the PSAD. On the other hand, Ferreira and collaborators (19) found a superiority of the PSADTZ in relation to the PSAD, however the PSADTZ was not better than the %FPSA.…”
Section: Commentsmentioning
confidence: 90%
See 1 more Smart Citation